Stature Prediction and Formulation of Regression Equation from Hand and Foot Anthropometry - Megha Rapotra; Jaswinder Kaur (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Estimation of stature is a key feature of personal identification. Evaluation of stature fromincomplete skeletal and decomposing human remains is particularly important in personal identification forforensic experts and anthropologists.Methods: The data was collected from 1000 asymptomatic, healthy adults (500 males and 500 females)belonging to border areas of Punjab region of age group ranged between 18-50 years.Results: The comparison of each parameter of the study shows that all parameters have higher valuesin males than in females. It is also observed that in males highest correlation is exhibited by Right footlength(r= .418) and in females it is exhibited by Left Foot Length (r= .354). The calculated linear regressionformulae show good reliability and applicability for stature estimation.Conclusion: In all parameters the foot length and hand length are better predictors of stature in both sex.Using regression formulae the height of subject can be easily determined and this will be used as researchtool in anthropological and medicolegal issues.